2015 Annual Conference of the North American Fuzzy Information Processing Society (NAFIPS) Held Jointly With 2015 5th World Con 2015
DOI: 10.1109/nafips-wconsc.2015.7284195
|View full text |Cite
|
Sign up to set email alerts
|

Type-2 fuzzy rule-based expert system for Ankylosing spondylitis diagnosis

Abstract: Ankylosing spondylitis (AS) is a chronic inflammatory disease. The pathogenesis of AS is poorly understood. However its association with human leukycyte antigen (HLA)-B27 is known. AS causes significant pain, disability, and social burden around the world [1]. Early diagnosis and treatment of AS are necessary in order to prevent or reduce all types of costs associated with loss of function. If the diagnosis is missed, however, the quality of patient's life will degrade. Besides, as a positive family history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It has already been shown the application of fuzzy logic and its effectiveness in the medical diagnosis of Ankylosing Spondylitis, anemia, dengue, thyroid, Alzheimer, Blood pressure, diabetes, and mental health, ontology-aided food and drug recommendation systems for a patient, etc. for identifying various disorders [5,[9][10][11][12][13][14][15]. Similarly, a lot of research is also going on to create an accurate, economical, and effective fuzzy logic-based expert system for diagnosing heart disease because the world health organization (WHO) reported that cardiovascular diseases (CVD) are now the main cause of death worldwide [5,[16][17][18][19].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…It has already been shown the application of fuzzy logic and its effectiveness in the medical diagnosis of Ankylosing Spondylitis, anemia, dengue, thyroid, Alzheimer, Blood pressure, diabetes, and mental health, ontology-aided food and drug recommendation systems for a patient, etc. for identifying various disorders [5,[9][10][11][12][13][14][15]. Similarly, a lot of research is also going on to create an accurate, economical, and effective fuzzy logic-based expert system for diagnosing heart disease because the world health organization (WHO) reported that cardiovascular diseases (CVD) are now the main cause of death worldwide [5,[16][17][18][19].…”
Section: Related Workmentioning
confidence: 99%
“…for identifying various disorders [5,[9][10][11][12][13][14][15]. Similarly, a lot of research is also going on to create an accurate, economical, and effective fuzzy logic-based expert system for diagnosing heart disease because the world health organization (WHO) reported that cardiovascular diseases (CVD) are now the main cause of death worldwide [5,[16][17][18][19]. Interestingly, the chance of mortality can be decreased by early diagnosis of heart diseases.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the information provided in Table V, Asl and Zarandi (2017) and Maftouni et al . (2015) have also designed several Type-2 fuzzy expert systems documented in conference papers.…”
Section: Particular Cases In Fuzzy Expert Systemsmentioning
confidence: 99%